Bancos comunitários de desenvolvimento como instrumento de políticas públicas: o caso do Banco Cidade de Deus - Medeiros, Amanda Cristina (2014)
The goal of this study was to investigate the challenges of the use of Community Development Banks as a tool of public policy. According to the Brazilian Network of Community Banks, the community banks are a group of solidary financial services, with associative and community nature, focused in generating work and earnings. Its intention is to re-organize local economies trough chains of solidary economy . Since its first inception–in Fortaleza/CE in 1998, the CDBs were replicated in 100 different places Because of its unique experience in dealing with microcredit and because of its capillarity in populations in poverty or extreme poverty situations these banks were launched as alternatives to some public policies of traditional microcredit, and have since been receiving support of the federal government to the replication of the existing experience and creation of new ones. Not only federal government but also state and local governments have been replicating the initiative, witch is the case in this study. Interviews and participant observation were used as tools in a qualitative study in the Community Bank of Cidade de Deus, located in Rio de Janeiro/RJ. The field study was conducted between May and August of 2014 and results indicate three challenging dimensions to the instrumentalization process of the CDBs as public policies They are: technical efficiency, financial sustainability and internal political conflicts.